Fiscal Capacity, Tax Potential, and Regional Revenue Independence in Palangka Raya - Vinita, Lesliana; Hukom, Alexandra; Zakiah, Wiwin (Institut Bisnis dan Informatika Kesatuan, 2025)
Local own-source revenue independence is essential for achieving fiscal autonomy and sustainable local development. This study aims to examine the influence of fiscal capacity, regional tax potential, and financial governance on local own-source revenue independence. A quantitative approach was employed using 40 quarterly data points, and multiple linear regression was applied to measure the direct and simultaneous effects of the three variables. The findings reveal that all independent variables positively and significantly affect local own-source revenue independence, with local tax potential exerting the strongest influence. This highlights the importance of optimizing tax potential through effective administration, digitalization, and taxpayer compliance. In addition, sound financial governance, characterized by transparency, accountability, and efficiency, enhances the utilization of fiscal resources, thereby strengthening fiscal independence. Collectively, these variables explain 81% of the variance in local own-source revenue independence, indicating a robust model. The study concludes that increasing local tax potential, combined with effective governance mechanisms, is critical for reducing reliance on external transfers and promoting fiscal autonomy. Policymakers are encouraged to focus on tax system reform, enhancing fiscal management capacity, and improving governance to support sustainable local economic development.